2007
DOI: 10.1074/jbc.m702269200
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase CK2 Phosphorylates SNAP190 to Negatively Regulate SNAPC DNA Binding and Human U6 Transcription by RNA Polymerase III

Abstract: In humans, polymerase specificity for snRNA 2 gene transcription depends upon the architecture of the core promoter region. snRNA genes containing solely a proximal sequence element (PSE) are transcribed by RNA polymerase II, whereas those containing juxtaposed PSE and TATA box elements are transcribed by RNA polymerase III (1). The human small nuclear RNA-activating protein complex (SNAP C ) is a general transcription factor that coordinates human snRNA gene transcription for both polymerases (2) through its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…PK3 does not have an obvious nuclear localization signal, and thus, its translocation may require interaction with importins, as was shown, for example, for mitogen-activated protein kinases (31). Similar to our observation that the SL RNA transcription complex disassembles during SLS in T. brucei, the promoter-binding transcription initiation complex of genes encoding snRNAs disassembles during M phase in mammalian cells (32). Mammalian U-rich snRNAs are synthesized by RNA pol II, with the exception of U6 snRNA, which is synthesized by RNA pol III.…”
Section: Discussionsupporting
confidence: 87%
“…PK3 does not have an obvious nuclear localization signal, and thus, its translocation may require interaction with importins, as was shown, for example, for mitogen-activated protein kinases (31). Similar to our observation that the SL RNA transcription complex disassembles during SLS in T. brucei, the promoter-binding transcription initiation complex of genes encoding snRNAs disassembles during M phase in mammalian cells (32). Mammalian U-rich snRNAs are synthesized by RNA pol II, with the exception of U6 snRNA, which is synthesized by RNA pol III.…”
Section: Discussionsupporting
confidence: 87%
“…For example, it has been shown that CK2 phosphorylates SNAP190, which in turn regulates SNAPc complex binding and transcription of the U6 snRNA gene by RNA polymerase III. 169 Clearly, therefore, the post-translational regulation of these 3 transcription complexes is largely unchartered territory and fertile ground for investigation.…”
Section: What Signals Promote Modification Of Cb Proteins?mentioning
confidence: 99%
“…The loss of promoter association by Bdp1 is sufficient to explain M-phase repression of snRNA expression. Although less pronounced, SNAP C promoter association is also diminished during M-phase [87], and may be attributable to CK2 phosphorylation of SNAP190 at a serine-rich region located adjacently to its Myb-DNA binding domain, which inhibits SNAP C recognition of the PSE [100].…”
Section: Cell Cycle Regulation Of Human Snrna Gene Transcriptionmentioning
confidence: 99%